2010
DOI: 10.1002/ejsp.719
|View full text |Cite
|
Sign up to set email alerts
|

It could have been better: The effects of counterfactual communication on impression formation

Abstract: While research on counterfactuals has closely examined the psychological antecedents and consequences of thinking counterfactually (imagining alternatives to past events), little is known about the effects of counterfactual communication, and in particular, how such thoughts are interpreted by others. In this paper, I argue that counterfactual communication differentially affects impressions formed of speakers by receivers depending on the general content of the counterfactual. Findings from an archival study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Interestingly, if the individual has the goal of presenting a favorable impression to others, claiming upward, otherfocused counterfactuals will backfire. Audiences apparently appreciate and evaluate more positively individuals who accept blame by communicating upward, self-focused counterfactuals (Wong, 2010).…”
Section: Other Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, if the individual has the goal of presenting a favorable impression to others, claiming upward, otherfocused counterfactuals will backfire. Audiences apparently appreciate and evaluate more positively individuals who accept blame by communicating upward, self-focused counterfactuals (Wong, 2010).…”
Section: Other Functionsmentioning
confidence: 99%
“…The foundational idea of the functional theory is that counterfactual thinking is illuminated through its connection to goal-directed cognition (Epstude & Roese, 2008, 2010, 2011Roese, 1997). In short, counterfactual thoughts often reflect goals and the varying means to reach those goals.…”
Section: Introductionmentioning
confidence: 99%
“…Counterfactuals are therefore likely to be effective when used as defensive statements. However, the use and effects of counterfactual defences and more generally of counterfactual communication have not been investigated extensively (but see Bertolotti, Catellani, Douglas, & Sutton, ; Catellani, ; Tal‐Or, Boninger, Poran, & Gleicher, ; Wong, ).…”
mentioning
confidence: 99%
“…Early research (Tal-Or, Boninger, Poran, & Gleicher, 2004) found that persuasive messages including counterfactual statements were more effective than messages not including counterfactual statements, but such effect persisted in the long term only when participants were prompted to generate themselves counterfactual thoughts. Subsequent studies analysed the use of counterfactuals in impression formation (Wong, 2010) and impression management (Bertolotti, Catellani, Douglas, & Sutton, 2013;Catellani & Bertolotti, 2014a, 2014b, showing that providing individuals with a counterfactual statement regarding an actor can effectively influence their judgements on the actor, the reconstructed event and even the source of the counterfactual statement itself. For instance, upward counterfactuals (e.g., "If he/she had acted in a different way, things would be better now") can be an effective form of implicit criticism, as they subtly imply that the actions of a chosen actor are causally linked to the outcome, and that the actor is therefore responsible for it (Catellani & Bertolotti, 2014b).…”
Section: The Effect Of Counterfactual Communication On Causal and Rmentioning
confidence: 99%